'Inappropriate but not crime'? Policing racial hatred in Sweden. Issue 1 (2nd January 2020) - Atak, Kıvanç
ABSTRACT: Racial bias afflicts police practices across the globe. Police discrimination against and mistreatment of racial and ethnic minorities is indeed difficult to underestimate. While much attention has been thus paid to racially biased policing, fewer studies examine the question from the reverse angle, namely how the police themselves combat racist offences. This article offers empirical insights into the policing of racial hatred in Sweden, a relevant yet relatively understudied case. Drawing on interviews with police officers and crime investigators, I discuss law enforcement perspectives, e.g. perceptions and reasoning in relation to the investigation of racist offences. Findings evince a rather narrow approach as regards the constructions of racist motive that involves a relatively restricted use of bias labelling in identifying hate incidents, especially when the boundaries of racial hostility are perceived as blurred. I argue that while such an approach may reflect a legitimate effort to demonstrate the existence of a motive behind an offence, it may also lead to an underestimation of more mundane forms of racism and their harms inflicted upon racialized individuals and communities. The results have implications for 'recognition' and 'belonging' as benchmarks of democratic policing, and 'the promise of inclusion' associated with combatting hate crimes.